Enucleation of radicular cyst in the maxillary area - Marito, Tresy Charlotte; Haryosuwandito, Erdananda; Arindra, Pingky Krisna; Sejati, Bramasto Purbo (Faculty of Dentistry, Universitas Gadjah Mada, 2025)
Radicular cyst is a true cyst that develops in association with a root of non-vital teeth. Radicular cyst is the most common cyst in the oral cavity with a percentage of 50% of all cysts in the oral cavity. Radicular cysts are usually asymptomatic and may cause swelling, tenderness, or tooth mobility. Another problem is due to the neoplastic transformation of the epithelial lining; however, this case is very uncommon. Management of radicular cysts consists of endodontic treatment, apicectomy on the root of non-vital teeth or decompression by enucleation, and extraction of the related teeth.A 63-year-old female patient came to RSGM Prof. Soedomo with a complaint of swollen gums in the area of upper front teeth that had been present for approximately a year with no associated pain. The patient previously had a panoramic X-ray examination, and the result revealed a radicular cyst. Biopsy aspiration results showed that there were cholesterol crystal-filled cysts. There was no history of systemic disease. The patient was treated by enucleation of the radicular cyst followed by extraction of the related teeth using general anesthesia. The patient was periodically evaluated postoperatively. The wound healing process was evaluated as expected, and the patient's complaints reduced. Clinical examination accompanied by radiographic examination and biopsy aspiration showed the presence of a radicular cyst. Treatment options, including cyst enucleation, depended on several factors, such as an expansion of the lesion, size and association of the cyst with surrounding tissue, as well as the patient’s systemic condition. Irrigation and drainage of the bone cavity and curettage of the remaining tissue should be done to ensure the lesion has been removed completely. The remaining bone spicules were shaped and smoothed, and primary wound closure was performed in order to minimize recurrency and complication.